Getting the Entire Message: Progress in Isoform Sequencing - Hardwick, Simon A.; Joglekar, Anoushka; Flicek, Paul; Frankish, Adam; Tilgner, Hagen U. (Frontiers in Genetics, 2019)
The advent of second-generation sequencing and its application to RNA sequencing has revolutionized the field of genomics by allowing the quantification of expression of entire genes as well as single TSS, exons and splice sites, RNA-editing sites as well as polyA-sites. However, due to the sequencing of fragments of cDNAs these methods have not given a reliable picture of complete RNA isoforms. Third-generation sequencing has filled this gap and allows end-to-end sequencing of entire RNA/cDNA molecules. This approach to transcriptomics has been a ‘niche’ technology for a couple of years but now is becoming mainstream with many different applications. Here, we review the background and progress made to date in this rapidly growing field. We start by reviewing the progressive realization that alternative splicing is omnipresent. We then focus on long-non-coding RNA isoforms and the distinct combination patterns of exons in non-coding and coding genes. We consider the implications of the recent technologies of direct RNA sequencing and single-cell isoform RNA sequencing. Finally, we discuss the parameters that define the success of long-read RNA sequencing experiments and strategies commonly used to make the most of such data.